Ore and Alteration Mineralogy of Paningkaban-Cihonje Gold Prospect, Gumelar Sub-district, Banyumas Regency, Central Java: A New Discovery of Carbonate Base Metal Gold Ephitermal Deposit - Idrus, Arifudin (2013)
The research area is located in Cihonje and Paningkaban Village, Gumelar Sub-District, banyumas Regency, Central java Province. The research area is found by many artisanal and small-scale gold miners (ASGM) are operating in that area. Based onthat, researchers wanted to know the types of deposits that reduce gold. In the research area there are several lineament which is estimated a fault line with the relative direction north-south, east-west, norhwest-southeast and northeast-southwest.